1977
DOI: 10.1177/002199837701100404
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of Boron/Aluminum Composites with Discontinuities

Abstract: Boron/aluminum laminates in symmetric layups of [±45] and [±45/02] containing discontinuities in the form of holes and slits were tested in tension. Both layups exhibited decreases in failure stress with discontinuity size. However the two exhibited quite different failure modes. The [±45 ] failed with interlaminar shear as the dominant mode whereas the [±45/02] specimens reacted to discontinuities catastrophically in a manner suggestive of the effect of cracks on homogeneous metals. A correlation is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The methods described below were chosen because they are representative of the different approaches to notched coupon fracture prediction/correlation, and because they have been shown to be good correlative models for coupon fracture stresses. The first method presented, developed by Mar and Lin [9], is similar in expression to linear elastic fracture mechanics but includes a factor accounting for the inhomogeneity of the material. The second, proposed by Whitney and Nuismer [10,11], is used to correlate fracture stresses by quantifying the local stress state surrounding the notch tip.…”
Section: Notched Flat Plates In Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods described below were chosen because they are representative of the different approaches to notched coupon fracture prediction/correlation, and because they have been shown to be good correlative models for coupon fracture stresses. The first method presented, developed by Mar and Lin [9], is similar in expression to linear elastic fracture mechanics but includes a factor accounting for the inhomogeneity of the material. The second, proposed by Whitney and Nuismer [10,11], is used to correlate fracture stresses by quantifying the local stress state surrounding the notch tip.…”
Section: Notched Flat Plates In Tensionmentioning
confidence: 99%
“…Mar and Lin describe the fracture stress of a notched coupon under uniaxial tension in a manner analagous to linear elastic fracture mechanics [9]. They proposed that the far-field fracture stress can be expressed in the form…”
Section: Notched Flat Plates In Tensionmentioning
confidence: 99%
“…Mar and Lin (ML-model) [12,58,59], is to assume: Table V. It can be seen from Figure 26 that Equation (13) represents the data quite closely.…”
mentioning
confidence: 94%
“…Several investigators have shown that the length of a discontinuity, not its shape, is the governing parameter, at least in fiber-dominated layups. [27][28][29] Thus, holes can be used to characterize the effect of other discontinuities, including slits. Further, it is shown in Chap.…”
Section: Introductionmentioning
confidence: 99%